2018
DOI: 10.3390/ma11030404
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces between Model Co-W-C Alloys with Various Carbon Contents and Tungsten Carbide

Abstract: Interfaces between alloys simulating binders in WC-Co cemented carbides and tungsten carbide were examined on the micro-, nano-, and atomic-scale. The precipitation of fine WC grains and η-phase occurs at the interface of the alloy with the low carbon content. The precipitation of such grains almost does not occur in the alloy with the medium-low carbon content and does not take place in the alloy with the high carbon content. The formation of Co nanoparticles in the binder alloy with the medium-low carbon con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The good properties were related to the elimination of mixed carbides (M 6 C and M 12 C) and WC/WC interfaces in structure. Some researchers like Konyashin et al [18] have studied the Co/WC interfaces. In this paper, we presented a developed Co-20% WC compound with good wear behaviour and performance.…”
Section: Introductionmentioning
confidence: 99%
“…The good properties were related to the elimination of mixed carbides (M 6 C and M 12 C) and WC/WC interfaces in structure. Some researchers like Konyashin et al [18] have studied the Co/WC interfaces. In this paper, we presented a developed Co-20% WC compound with good wear behaviour and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the cermet coatings, represented by WC-Co, exhibit better corrosion resistance and wear resistance. Simultaneously, owing to the existence of metal binder, the coating has better toughness under the premise of maintaining high hardness [7][8][9][10]. Its main anti-corrosion principle is to form an aluminum-rich phase as a protective film to isolate the molten zinc aluminum.…”
Section: Introductionmentioning
confidence: 99%
“…Fabijanić et al [20] found that the addition of 0.45% Cr 3 C 2 in WC contributed to microstructure homogeneity and reduced discontinuous and continuous grain growth, which increased Vickers hardness by approximately 70 HV and fracture toughness by approximately 0.15 MN/m 3/2 . Konyashin et al [21] observed the phenomenon of precipitating fine grains of WC and η-phase in the interface region of a binder model alloy with low carbon content. Armstrong [22] found that the mean free path dimensions of Co binder were important in affecting the composite material toughness properties and fracturing behavior of internal thermal micro-stresses.…”
Section: Introductionmentioning
confidence: 99%